Optimalisasi Perencanaan Strategik Pembelajaran Dalam Meningkatkan Mutu Lulusan Era Digital - Suharyanto H. Soro; Enden Hayati; Dewi Tejawati; Asti Susanti (LP. Ma'arif Janggan Magetan, 2024)
Planning is carried out based on data obtained through mapping and identification activities carried out by educational units. The formulation of planning involves all elements, including school principals, teachers, students, stakeholders. This is done to ensure that the items or points that make up the school's program (planning) can be accepted by all parties. However, formulating a plan is not a simple activity because there are many factors that are taken into consideration and there can even be clashes of ideas or opinions about the main points or programs that are priorities in a certain period. This research aims to identify strategic steps implemented in digital-based learning planning to improve the quality of education. era of globalization. In other words, the research focus includes exploring various initiatives, such as the integration of technology in the learning process, teacher competency training, and the provision of digital learning support facilities. Apart from that, this research also aims to identify the obstacles faced in the process of optimizing strategic planning, including infrastructure limitations, and examine the solutions implemented to overcome these challenges. Researchers use a qualitative research paradigm. Data collection methods use observation, interviews and documentation studies. The sample in the study was selected based on purposive sampling. Researchers took a sample of 20 people. They are people who are directly involved in the educational unit's strategic planning process. Research activities will be carried out in the 2024 academic year. The resuls of the research showed that previous learning at SDN Cikuya 03 was dominated by traditional methods with limited use of technology. The main obstacles were the minimal technology infrastructure and teachers' low digital competence. To overcome this, the school adopted strategies such as teacher training, the use of Google Classroom Learning Management System (LMS), and interactive learning with applications such as Kahoot and Quizizz. Optimizing this strategy has had a positive impact, as seen in the improvement of student grades, digital literacy, and active participation in learning. However, challenges such as limited infrastructure and variations in teachers' abilities still need to be addressed.